“LEGAL STANDING” AND “THE DEMAND” IN SECTION 165 OF THE COMPANIES ACT 71 OF 2008: A COMPARATIVE DISCUSSION - Darren Subramanien (Obiter, 2022)
Section 165 of the Companies Act 71 of 2008 provides that applicants with locus standi who are aware of a wrong perpetrated against the company and who wish to pursue a derivative action against the company must have served a demand on the company requiring it to commence or continue legal proceedings to protect its own legal interests. Thereafter, the company must have filed a notice indicating that the company refuses to comply with the demand, or alternatively, the company must have failed to comply at all or failed to comply properly with its obligations relating to the investigation of the demand and its response to the demand. This article explores the concepts of legal standing and the demand that must be served on the company requiring it to commence or continue legal proceedings to protect its own legal interests as contemplated in section 165(2) of the 2008 Act, with the aim of identifying the commendable aspects of these concepts as well as the possible shortfalls.